Review of Management and Outcomes in Women with Thrombophilia Risk during Pregnancy at a Single Institution. (17th February 2014) - Khalafallah, Alhossain A.; Ibraheem, Abdul-Rauf O.; Teo, Qiong Yue; AlBarzan, Abdul-Majeed; Parameswaran, Ramanathan; Hooper, Emily; Pavlov, Toly; Dennis, Amanda E.; Hannan, Terry
Abstract : Pregnancy is a hypercoagulable state associated with an increased risk of venous thromboembolic disease (VTE). We retrospectively studied 38 Caucasian pregnant women with thrombophilia risk and compared their obstetric outcomes with a matched cohort without known thrombophilia risk during the period between January 2007 and December 2010. There were (2) cases with factor V Leiden, (6) prothrombin gene mutation, (1) antithrombin III deficiency, (2) protein C deficiency, (3) protein S deficiency, (10) MTHFR mutation, (7) anti-cardiolipin antibodies, and (1) lupus anticoagulant. Patients without thrombophilia who presented with recurrent unprovoked VTE were considered as high risk (6 cases). Most patients received anticoagulation (34/38) with aspirin only (6), enoxaparin (27), and warfarin (1). Twenty-six out of thirty-eight pregnant women (68.4%) with an increased risk of thrombophilia experienced one or more obstetric complications defined as hypertension, preeclampsia, placenta abruptio, VTE, and oligohydramnios, compared with 15 out of 40 (37.5%) pregnant women in the control group (OR 3.6; 95% CI 1.42, 9.21, P < 0.001 ). The incidence of obstetric complications was significantly higher in the thrombophilia group compared to the controls. However, these complications were the lowest among patients who received full-dose anticoagulation. Our study suggests that strict application of anticoagulation therapy for thrombophilia of pregnancy is associated with an improved pregnancy outcome. The study was registered in the Australian and New Zealand Clinical Trials Registry under ACTRN12612001094864 .